Prospect of food bolus obstruction in a tertiary care hospital - Naqvi, Raheel Hussan; Gupta, Aaina; Khokher, Bhanu; Dhar, Surbhi; Gupta, Shaarang (International Surgery Journal, 2022)
Background: Small bowel obstruction (SBO) is a common general surgical emergency usually caused by adhesions, bands or hernias. Food bolus impaction or bezoars remain an uncommon cause, albeit well reported in literature. The objective was to outline the frequency, demographic features, etiopathogenesis and management patterns of acute SBO due to ingested food bolus. Methods: An observational retrospective study was conducted whereby patients admitted to the surgical emergency of the associated hospital of Government Medical College, Jammu, Jammu and Kashmir, India as cases of acute SBO, who underwent laparotomy, over a period extending from August 2020 to June 2022 were selected and their records reviewed for history of ingestion/intra-operative finding of food bolus obstruction. Demographic, etiological and management patterns were noted. Descriptive analysis was done using Jamovi (version 1.6) (computer software). Results: A total of 100 patients of food bolus obstruction were admitted and operated upon during the study period with a median age of 14 years, with 40% patients belonging to 11 to 20 years age group, with a male to female ratio of 3:1. Majority belonged to rural areas (86%). 97% cases were due to ingestion of date plum or persimmons (vernacular: “amlook”). Ileum was the most common site of impaction (63%). 90% cases were managed by fragmentation of bolus and milking of gut, whereas enterotomy and resection-anastomosis were performed in 5 patients each. Conclusions: Food bolus obstruction especially due to phytobezoars of Diospyros lotus (date plum or “Amlook”) is often encountered in our setup, especially in rural populations, predominantly affecting male children and adolescents.